Corporate Social Responsibility and Earnings Management: The Moderating Role of Corporate Governance - Wati, Erna; Malik, Abdul Qaadir (Journal of Accounting Research, Organization and Economics, 2021)
Objective This study investigates the relationship between corporate social responsibility (CSR) and earnings management (EM) with corporate governance (CG) as the moderating variable.Design/methodology This study uses data collected from public companies listed in Indonesia Stock Exchange which include the audited annual reports and published sustaina-bility report during the year 2016 2019. The regression model was used to estimate the co-efficient of EM and CSR.Results This study finds EM has an insignificant negative relationship with CSR and CG as a moderating effect. This indicates that the implementation of CSR in Indonesia does not affect EM with the involvement of CG as moderating variable. CG is playing an important role in monitoring the management so that managers do not override the company interest. Thus, CG has an effort to maintain the stability of interest between the stakeholders and managers.Limitation/Suggestion This study is limited in its sample size resulted from the una-vailability of some annual reports and sustainability reports. The findings of this study has implications for company managers, and shareholders. It assists the company management to develop and implement strategies that will strengthen the CG structure, especially in de-veloping countries, to protect shareholders and increase stock exchange confidence. It also contributes in enhancing the previous literature research on the relationship between CSR and EM moderated by CG by showing how CG can influence the relationship between CSR and EM.